Studies on Carcinoma of the Stomach after Gastric Surgery: A Review of 10 Cases - SASAKI, Akira; KOBAYASHI, Genso; TANEMOTO, Kazuo; YAMASHITA, Hiroshi; OOISHI, Masahiro; TANAKA, Toshiaki; KONAGA, Eiji; TAKEUCHI, Hitoshi (Japanese Journal of National Medical Services, 1989)
Ten cases of carcinoma of the stomach after gastric surgery were examined. The average age of cases was 56.9 and the sex of them was predominantly male. Diagnosis of initial surgery were benign gastric disease (5 cases) and gastric carcinoma (5 cases). Billroth-II method without Braun anastmosis was chosen mainly for initial gastrectomy. The average interval between initial and subsequent surgery was 14.4 years in the cases of benign gastric diseases and 9.4 years in gastric carcinoma. Symptoms such as swallowing disturbances and epigastralgia were frequently seen in advanced carcinoma of the remnant stomach. Early stage of carcinoma was diagnosed by endoscope and biopsy. The methods of second operation were total resection of the remnant stomach (7 cases) and palliative surgery (3 cases): 5 cases underwent curative resection and 2 noncurative resection. Since the carcinoma of the remnant stomach was advanced, combined resection of spleen and/or tail of the pancreas was often done. Carcinomas of the resected remnant stomach were 3 early carcinomas (2 cases of type IIa, one type IIa+IIc) and 4 advanced carcinomas (2 cases of Borrmann 3, 2 cases of Borrmann 4). Cases of the curative resection survived three years and one month longer. Most of the noncurative cases and palliative surgery cases died in a year. Histologic examination of the resected remnant stomach revealed mild atrophic gastritis (all cases) and moderate intestinal metaplasia (a few cases) which were said to be precancerous changes. We conclude that several factors to improve the prognosis of surgery for carcinoma of the remnant stomach are as follows: 1) periodic follow-up and examination of diagnosis of early stage of cancer 2) total resection of the remnant stomach with combined resection of adjacent organs for complete lymphnode dissection.